2004
DOI: 10.1090/s0002-9939-04-07337-x
|View full text |Cite
|
Sign up to set email alerts
|

Puiseux parametric equations of analytic sets

Abstract: Abstract. We prove the existence of local Puiseux-type parameterizations of complex analytic sets via Laurent series convergent on wedges. We describe the wedges in terms of the Newton polyhedron of a function vanishing on the discriminant locus of a projection. The existence of a local parameterization of quasi-ordinary singularities of complex analytic sets of any codimension will come as a consequence of our main result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Corollary 2. (Aroca, [2]) Let X be an algebraic variety of C N +M , 0 ∈ X, dim(X) = N. Let U be a neighborhood of 0, and let π be the restriction to X ∩ U of the projection (z 1 , ..., z N +M ) → (z 1 , ..., z N ). Assume π is a finite morphism.…”
Section: -The Series Development Of the Parameterizationsmentioning
confidence: 99%
“…Corollary 2. (Aroca, [2]) Let X be an algebraic variety of C N +M , 0 ∈ X, dim(X) = N. Let U be a neighborhood of 0, and let π be the restriction to X ∩ U of the projection (z 1 , ..., z N +M ) → (z 1 , ..., z N ). Assume π is a finite morphism.…”
Section: -The Series Development Of the Parameterizationsmentioning
confidence: 99%
“…The following is an easy but frequently useful lemma (see [7,Lemma 4.7] or [52,6.VI] or [41,Lemma 4.3] for a proof) concerning the ordering of fractional normal crossings and their exponents.…”
Section: Remarksmentioning
confidence: 99%
“…Let σ be a strongly convex cone that contains the first orthant. In [3] it is shown that (when it is not empty) the domain of convergence of a series with exponents in a strongly convex cone σ contains an open set W that has the origin as accumulation point. Moreover, by the results of [3,Prop 3.4], the intersection of a finite number of such domains is non-empty.…”
Section: The Local Parametrizations Defined By the Seriesmentioning
confidence: 99%
“…Quasi-ordinary singularities admit analytic local parametrizations. This was shown for hypersurfaces by S. Abhyankar [1] and extended to arbitrary codimension in [3]. Quasi-ordinary singularities have been the object of study of many research papers [8, 15, 32, 28, ...].…”
Section: The Solutionsmentioning
confidence: 99%
See 1 more Smart Citation